Salvage therapy with bortezomib and dexamethasone in elderly patients with relapsed/refractory multiple myeloma. Issue 10 (November 2015) - Castelli, Roberto; Pantaleo, Giuseppe; Gallipoli, Paolo; Gidaro, Antonio; Arquati, Massimo; Wu, Maddalena A.; Lambertenghi Deliliers, Giorgio
Abstract : Bortezomib–dexamethasone (bort–dex) is effective for relapsed/refractory (R/R) multiple myeloma, but few data are available for elderly patients. The aim of this study was to evaluate efficacy and toxicity of bort–dex in elderly R/R MM patients. We evaluated 81 R/R MM patients treated with bort–dex. Eight of them had light-chain disease. The median age of the patients was 73 years (range 65–89 years). All patients were R/R MM patients and had been treated with melphalan and prednisone with or without thalidomide or bortezomib in the first line or with lenalidomide and dexamethasone in the second line. The median number of previous lines was 2. Thirty-nine (48%) patients received bortezomib intravenously and 42 (52%) patients received bortezomib subcutaneously. The median number of bort–dex cycles was 6 (range 1–11). Fifty-three (65.4%) patients achieved at least a partial response, including eight (11%) patients with complete response and nine (12.5%) patients with very good partial responses. The median duration of response, time to next therapy and treatment-free intervals were 8, 11 and 5 months. Duration of response was significantly longer for patients achieving complete response/very good partial response than for those achieving partial response (7.3 vs. 3.8 months, P =0.03). After a median follow-up of 24 months, 78 patients showed disease progression and 70 died. The median time to progression, progression-free survival and overall survival were 8.9, 8.7 and 22 months, respectively. Peripheral neuropathy occurred in 38 (47%) patients. Our data highlight that bort–dex is effective and tolerable in fit elderly patients, thus justifying the efforts for deeper responses. However, awareness of short-lived responses to bort–dex should lead to a thorough evaluation of the need for maintenance.